Perfil de susceptibilidad por Enterococcus sp como responsable de infecciones nosocomiales en Latinoamérica. - Haro Santamaría, Stefany Valeria (2022)
ABSTRACT: The genus Enterococcus is a microorganism immersed in nosocomial infections, and it is vitally important to know it. This research was carried out through a bibliographic review to collect scientific information on the susceptibility profile of this pathogen as responsible for these entities. It is a descriptive, documentary, and non-experimental, retrospective study, where 68 scientific articles were reviewed, and 50 articles were selected through the inclusion and exclusion criteria. The information was searched in Elsevier, Global Nursing, Scielo, Infomed, Fucs, Redalyc, Dialnet, Medigraphic, Pubmed, Medicine U.P.B, Proquest, MEDWave, JIDC, and books. With the analysis and discussion of the different authors, the research was concluded, achieving the proposed objective, in which it was evidenced that the clinically isolated Enterococcus species were E. faecalis, E. faecium. E. gallinarum and E. casseliflavus, the former being the most common, causing bacteremia, sepsis of the surgical site and urinary tract, associated with using catheters, probes, extended hospital stay, age, and underlying diseases. Regarding susceptibility and resistance, it was found that E. faecium presented resistance to ampicillin, vancomycin, and tigecycline, while E. faecalis was resistant to gentamicin, quinupristin/dalfopristin, and both to linezolid. The most commonly used diagnostic methods were the conventional microbiological tests, the Kirby Bauer, the Minimum Inhibitory Concentration, and the Polymerase Chain Reaction. Accurately, these aspects prevent major complications that lead to a prolonged patient stay in the hospital environment. Keywords: Enterococcus, nosocomial infection, E. faecalis, E. faecium, antimicrobial susceptibility